2020
DOI: 10.1074/mcp.tir120.002061
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Microorganisms by Liquid Chromatography-Mass Spectrometry (LC-MS1) and in Silico Peptide Mass Libraries

Abstract: Over the past decade, modern methods of mass spectrometry (MS) have emerged that allow reliable, fast and cost-effective identification of pathogenic microorganisms. While MALDI-TOF MS has already revolutionized the way microorganisms are identified, recent years have witnessed also substantial progress in the development of liquid chromatography (LC)-MS based proteomics for microbiological applications. For example, LC-tandem mass spectrometry (LC-MS2) has been proposed for microbial characterization by means… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 49 publications
0
39
0
Order By: Relevance
“…n. s. o. r. t. i. u. m. UniProt, 2019). Therefore, we utilized a LC-MS 1 based method for microbial species identification, which has been adopted from MALDI-ToF MS biotyping and relies on LC-MS 1 pattern analysis (Lasch et al , 2020). The proteome of the identified species is then employed for predicting a sample-specific spectral library, which are in turn used as a background for peptide identification from the Comprehensive Antibiotic Resistance Database (CARD) (Alcock et al , 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…n. s. o. r. t. i. u. m. UniProt, 2019). Therefore, we utilized a LC-MS 1 based method for microbial species identification, which has been adopted from MALDI-ToF MS biotyping and relies on LC-MS 1 pattern analysis (Lasch et al , 2020). The proteome of the identified species is then employed for predicting a sample-specific spectral library, which are in turn used as a background for peptide identification from the Comprehensive Antibiotic Resistance Database (CARD) (Alcock et al , 2020).…”
Section: Resultsmentioning
confidence: 99%
“…This enables the use of DIA-based proteomics, which records the entity of peptide fragments in a sample above its sensitivity threshold in an unbiased manner with deep proteome coverage. The prediction of sample-specific background libraries for AMR detection is based on the results of a recently introduced strategy for biotyping bacteria using LC-MS 1 data, whose recording can easily be integrated into DIA measurements (Lasch et al , 2020). This approach resulted in an identification accuracy of 93 % with a runtime of ~ 1 min on a decent desktop PC using a database with 8540 bacterial entries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, mix-microbial identification by MALDI-TOF MS has used specific algorithms to determine the mass spectra biomarkers for microorganisms [ 47 ]. Meanwhile, liquid chromatography–tandem MS is also used to identify mix-microbial samples [ 48 , 49 ]. As the mass spectral database grows significantly, yeast identification using MS, including identification of mix-culture, would be expected in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…As one example, results from the study of Roux–Dalvai and colleagues [ 38 ] revealed that an HPLC-MS-based assessment of peptides, followed by the establishment of a set of unique peptide signatures using machine learning methods (i.e., top-down approach) resulted in the direct identification of fifteen distinct pathogenic bacterial species in urine specimens. Moreover, if the acquired peptide signatures are systematically evaluated using an in silico library generated from public databases (e.g., Swiss–Prot and Translated EMBL Nucleotide Sequence Data Library (TrEMBL); a bottom-up approach), the number of identifiable isolates can be increased to include more than 12,000 bacterial strains [ 59 ]. However, the transfer of these approaches to routine clinical laboratories remains limited and MALDI-TOF MS devices remain the most prominent at this time [ 38 ].…”
Section: Methods For Identifying Infectious Agentsmentioning
confidence: 99%